The rights of war and peace - Grotius, Hugo, 1583-1645 (Natural law and enlightenment classics., 2005)
Laying the foundation for a universal code of law, this is a work in modern public international law. It was considered to be a major work of political theory that defended the rights of individual agents - states as well as private persons - to use their power to secure themselves and their property.